Explicación paso a paso:
Resolución:
a)
[tex]2^{2x}-5(2^x)+4=0[/tex]
[tex](2^x)^2-5(2^x)+4=0[/tex]
Hacemos un cambio de variable donde:
[tex]a=2^x[/tex]
Operamos:
[tex](a)^2-5(a)+4=0[/tex]
[tex]a^2-5a+4=0[/tex]
Factorizamos:
[tex](a-4)(a-1)=0[/tex]
Sacamos raíces:
[tex]a= 4[/tex] [tex]a=1[/tex]
Deshacemos el cambio de variable:
[tex]2^x=4[/tex] [tex]2^x=1[/tex]
[tex]2^x=2^2[/tex] [tex]2^x=2^0[/tex]
[tex]x_1=2[/tex] [tex]x_2=0[/tex]
Solución:
[tex]x_1=2[/tex] [tex]x_2=0[/tex]
----------------------------------------------------------------------------------------------------------
b)
[tex]4^x-3(2^{x+1})+8=0[/tex]
[tex](2^2)^x-3(2^x*2)+8=0[/tex]
[tex](2^x)^2-3(2^x*2)+8=0[/tex]
Hacemos un cambio de variable donde:
[tex]b=2^x[/tex]
Operamos:
[tex](b)^2-3(b*2)+8=0[/tex]
[tex]b^2-3(2b)+8=0[/tex]
[tex]b^2-6b+8=0[/tex]
Factorizamos:
[tex](b-4)(b-2) =0[/tex]
Sacamos raíces
[tex]b=4[/tex] [tex]b=2[/tex]
Deshacemos el cambio de variable:
[tex]2^x=4[/tex] [tex]2^x=2[/tex]
[tex]2^x=2^2[/tex] [tex]2^x=2^1[/tex]
[tex]x_1=2[/tex] [tex]x_2=1[/tex]
Solución:
[tex]x_1=2[/tex] [tex]x_2=1[/tex]
--------------------------------------------------------------------------------------------------------
c)
[tex]2^{x-1}+\frac{1}{2^{x-3}}=5[/tex]
[tex]2^x*2^{-1}+\frac{1}{2^x*2^{-3}}=5[/tex]
Hacemos un cambio de variable donde:
[tex]c=2^x[/tex]
Operamos:
[tex]c*2^{-1}+\frac{1}{c*2^{-3}} =5[/tex]
[tex]\frac{c}{2 } +\frac{1}{\frac{c}{2^3} } =5[/tex]
[tex]\frac{c}{2} +\frac{2^3}{c} =5[/tex]
[tex]\frac{c(c)+2(2^3)}{2c}=5[/tex]
[tex]\frac{c^2+2^4}{2c}=5[/tex]
[tex]c^2+16=5(2c)[/tex]
[tex]c^2+16=10c[/tex]
[tex]c^2-10c+16=0[/tex]
Factorizamos:
[tex](c-8)(c-2)=0[/tex]
Sacamos raíces:
[tex]c=8[/tex] [tex]c=2[/tex]
Deshacemos el cambio de variable:
[tex]2^x=8[/tex] [tex]2^x=2[/tex]
[tex]2^x=2^3[/tex] [tex]2^x=2^1[/tex]
[tex]x_1=3[/tex] [tex]x_2=1[/tex]
Solución:
[tex]x_1=3[/tex] [tex]x_2=1[/tex]
---------------------------------------------------------------------------------------------------------
d)
[tex]4^x+2^5=3(2^{x+2})[/tex]
[tex](2^2)^x+2^5=3(2^x*2^2)[/tex]
[tex](2^x)^2+2^5=3(2^x*2^2)[/tex]
Hacemos un cambio de variable donde:
[tex]d=2^x[/tex]
Operamos:
[tex](d)^2+2^5=3(d*2^2)[/tex]
[tex]d^2+32=3(4d)[/tex]
[tex]d^2+32=12d[/tex]
[tex]d^2-12d+32=0[/tex]
Factorizamos:
[tex](d-8)(d-4)=0[/tex]
Sacamos raíces:
[tex]d=8[/tex] [tex]d=4[/tex]
Deshacemos el cambio de variable:
[tex]2^x=8[/tex] [tex]2^x=4[/tex]
[tex]2^x=2^3[/tex] [tex]2^x=2^2[/tex]
[tex]x_1=3[/tex] [tex]x_2=2[/tex]
Solución:
[tex]x_1=3[/tex] [tex]x_2=2[/tex]